(untitled) (Pedagogy of Higher and Secondary Education, 2011)
The question of harmony of intellect and emotions is examined in the article as a factor of a professional succes of a future teacher. The arguments of existence of close intercommunication between an intellect and emotions are resulted from the psychological and pedagogical point of view.